Elevated INR in a COVID-19 patient after concomitant administration of azvudine and anticoagulants - Zhang, Xi; Jiao, Fengwei; Li, Guangrun; Yu, Xiaojia; Pei, Yuqing; Zhang, Ying; Wang, Zihui; Li, Pengfei (Frontiers in Pharmacology, 2023)
Background: Azvudine (FNC) is a promising treatment candidate for managing coronavirus disease 2019 (COVID-19). But drug interactions with azvudine have been poorly studied, especially with no reported cases of azvudine with anticoagulants such as warfarin and rivaroxaban. Case summary: The patient was diagnosed with lower limb venous thrombosis and took warfarin regularly. The international normalized ratio (INR) was stable (2.0 to 3.0). However, INR increased to 7.52 after administering azvudine. The patient had no other factors justifying this change. This increase in INR occurred again with azvudine in combination with rivaroxaban, INR rose as high as 18.91. After azfudine was stopped, INR did not increase when rivaroxaban was used alone. Conclusion: Azvudine and warfarin, rivaroxaban might have previously unidentified drug interactions that elevated the INR. Therefore, INR must be closely monitored when they are concomitantly administered in COVID-19 patients.